Fun(ctional) equation #2

Algebra Level 4

2 f ( x ) = f ( x y ) + f ( x y ) 2f(x)=f(xy)+f\left(\dfrac{x}{y}\right)

If the above equation is true for all x , y R + x,y\in \mathbb{R}^{+} and f ( 1 ) = 0 , f ( 1 ) = 1 f(1)=0, f'(1)=1 , then find the closed form of f ( 1000 ) f(1000) to 3 decimal places.


The answer is 6.908.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Mark Hennings
May 12, 2017

The condition f ( 1 ) = 0 f(1) = 0 is implied by the functional equation (put x = y = 1 x=y=1 ). If we define the function g ( x ) = f ( e x ) g(x) = f(e^x) , then the function g g satisfies the equations g ( x + y ) = g ( x ) + g ( y ) ( x , y R ) g ( 0 ) = 0 , g ( 0 ) = 1 g(x+y) \; = \; g(x) + g(y) \hspace{1cm} (x,y \in \mathbb{R}) \hspace{2cm} g(0) = 0\,,\,g'(0) = 1 Thus we are assuming that g g is differentiable at 0 0 , and hence is continuous at 0 0 . Since g ( x + h ) g ( x ) = g ( h ) = g ( h ) g ( 0 ) x , h R g(x+h) - g(x) \; = \; g(h) \; = \; g(h) - g(0) \hspace{2cm} x,h \in \mathbb{R} it follows that g g is continuous everywhere.

It is a simple matter of induction to show that g ( m x ) = m g ( x ) g(mx) = mg(x) for all x R x \in \mathbb{R} and m Z m \in \mathbb{Z} , and since n g ( m n x ) = g ( m x ) = m g ( x ) x R , m , n Z , n 0 ng\big(\tfrac{m}{n}x\big) \; = \; g(mx) \; = \; mg(x) \hspace{2cm} x \in \mathbb{R}\,,\,m,n \in \mathbb{Z}\,,\, n \neq 0 we deduce that g ( q x ) = q g ( x ) q Q , x R g(qx) \; = \; qg(x) \hspace{2cm} q \in \mathbb{Q}\,,\,x \in \mathbb{R} In particular, therefore, q ( q ) = q g ( 1 ) q(q) = qg(1) for q Q q \in \mathbb{Q} . Since g g is continuous everywhere and the rationals are dense in the reals, it follows that g ( x ) = k x g(x) = kx for all real x x , where k = g ( 1 ) k = g(1) . Thus k = g ( 1 ) = 1 k = g'(1) = 1 , and hence g ( x ) = x g(x) = x . This implies that f ( x ) = ln x f(x) = \ln x for all x > 0 x > 0 , making the answer ln 1000 = 6.907755279 \ln1000 = \boxed{6.907755279} .

The condition that f ( 1 ) = 1 f'(1) = 1 is key, since it implies the continuity of g g . There are infinitely many examples of discontinuous functions g g on R \mathbb{R} satisfying the identity g ( x + y ) = g ( x ) + g ( y ) g(x+y) = g(x) + g(y) for all x , y x,y . Equivalently, there are infinitely many examples of discontinuous functions f f satisfying the main functional equation.

Aakash Khandelwal
May 14, 2017

Step 1: Differentiate equation w.r.t. x x and then put x = 1 a n d y = x x= 1 and y=x .

Step 2: Differentiate equation w.r.t. to y y and then put y = 1 y= 1

By solving both equations simultaneously one easily gets 1 = x × d y / d x 1= x\times dy/dx ,Taking y = f ( x ) y=f(x) .

Solve this elementary diffrential equation.

I'm not getting it. Please make it more detailed

Sid Patak - 3 years, 11 months ago
Nivedit Jain
Jun 11, 2017

By hit and error f(x) = lnx

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...